Implementasi Metode Manhaji dalam Pembelajaran Tafhimul Qur’an Siswa Boarding School Kelas VIII A di MTS Muhammadiyah 1 Klaten - Syuhudi, Alfani (Pascasarjana UIN Raden Mas Said Surakarta, 2021)
AbstractImplementation of the Manhaji Method in Tafhimul Quran Learning for Class VIII A Boarding School students at MTS Muhammadiyah 1 Klaten. The Quran is a way of life for Muslims. Allah has sent down the Quran as a book in which there are His instructions. Therefore, Allah also ordered Muslims to study the Quran. Because of the importance of learning the Quran, MTs Muhammadiyah 1 Klaten provides Tafhimul Quran subjects which are new subjects, so we need a manhaji method which this method has been used by Islamic Boarding School of Muhammadiyah. The purpose of this paper is to find out how the application of the manhaji method in learning Tafhimul Quran, as well as the driving and inhibiting factors of this method. This research is a field research with a qualitative descriptive approach. The results of this study indicate that the application of the manhaji method in Tafhimul Quran learning has proven to be very satisfying, namely that most students have reached the KKM score, because this method has a gradual way in the learning process so that students do not feel burdened and do not find it difficult to follow it.Keywords: Implementation, Manhaji Method, Tafhimul Quran Learning